2020
DOI: 10.1186/s12890-020-01264-x
|View full text |Cite
|
Sign up to set email alerts
|

Operative invasiveness does not affect the prognosis of patients with non-small cell lung cancer

Abstract: Background The relationship between operative invasiveness and the prognosis in non-small cell lung cancer (NSCLC) patients who have undergone surgery has been controversial. Methods Clinical data were analyzed for 463 NSCLC patients. Operative invasiveness was defined by wound length, operation time, and the postoperative C-reactive protein (postCRP) level. The operative approach was divided into video-assisted thoracic surgery (VATS) and thoracotomy. Results The wound length and operation time were signi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…However, the relationship between prognosis and operative approaches such as VATS or RATS in NSCLC patients who have undergone pulmonary resection has not been elucidated. Our previous study revealed that operative invasiveness does not affect the prognosis of patients with NSCLC [29]. Because VATS and RATS were not prognostic factors in the present study, the operative approach therefore does not in uence the prognosis of NSCLC patients.…”
Section: Discussioncontrasting
confidence: 45%
“…However, the relationship between prognosis and operative approaches such as VATS or RATS in NSCLC patients who have undergone pulmonary resection has not been elucidated. Our previous study revealed that operative invasiveness does not affect the prognosis of patients with NSCLC [29]. Because VATS and RATS were not prognostic factors in the present study, the operative approach therefore does not in uence the prognosis of NSCLC patients.…”
Section: Discussioncontrasting
confidence: 45%
“…In fact, in addition to the macroscopic indexes of clinical trauma, the evaluation of the effects of the two kinds of surgery can also be analyzed in the macroscopic aspect. In the case of infection or some tissue damage, CRP content usually increases rapidly, and it is a non-specific inflammatory marker (17,18). In this study, the serum CRP levels in the observation group at each time point postoperative were significantly lower than those in the control group.…”
Section: Discussionmentioning
confidence: 46%
“…Originally, glycolysis was considered important for tumor metabolism and growth, manifesting as a heightened glucose uptake rate [ 4 ]. We previously reported that smoking history, vascular invasion, and pStage, but not postoperative complications, were identified as significant prognostic factors in a multivariate analysis of 463 patients with NSCLC [ 24 ]. Recently, however, we showed the clinical relevance of SGLT2 in resected lung adenocarcinoma, and the expression of SGLT2 was more frequently detected in advanced-stage and more aggressive adenocarcinomas with aggressive biological behavior than in their counterparts.…”
Section: Discussionmentioning
confidence: 99%